Corticotropin-releasing factor system in the lateral septum: Implications in the pathophysiology of obesity - Olivares-Barraza, Rossy; Marcos, José Luis; Martínez-Pinto, Jonathan; Fuenzalida, Marco; Bravo, Javier A.; Gysling, Katia; Sotomayor-Zárate, Ramón (Frontiers in Molecular Neuroscience, 2022)
Obesity is a pandemic associated with lifestyles changes. These include excess intake of obesogenic foods and decreased physical activity. Brain areas, like the lateral hypothalamus (LH), ventral tegmental area (VTA), and nucleus accumbens (NAcc) have been linked in both homeostatic and hedonic control of feeding in experimental models of diet-induced obesity. Interestingly, these control systems are regulated by the lateral septum (LS), a relay of γ-aminobutyric (GABA) acid neurons (GABAergic neurons) that inhibit the LH and GABAergic interneurons of the VTA. Furthermore, the LS has a diverse receptor population for neurotransmitters and neuropeptides such as dopamine, glutamate, GABA and corticotropin-releasing factor (CRF), among others. Particularly, CRF a key player in the stress response, has been related to the development of overweight and obesity. Moreover, evidence shows that LS neurons neurophysiologically regulate reward and stress, although there is little evidence of LS taking part in homeostatic and hedonic feeding. In this review, we discuss the evidence that supports the role of LS and CRF on feeding, and how alterations in this system contribute to weight gain obesity.